2015
DOI: 10.2215/cjn.07760814
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and Mortality in Dialysis

Abstract: A higher severity of frailty (as defined by the CFS) at dialysis initiation is associated with higher mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
174
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(192 citation statements)
references
References 41 publications
13
174
1
4
Order By: Relevance
“…All four studies found a positive association of the presence of frailty with adverse health outcomes. Frailty at dialysis initiation was associated with a higher risk of mortality (45)(46)(47)(48) and hospitalization (45,46,48), independent of age and other possible risk factors for poor outcome. In the largest study in 2275 patients on incident dialysis of all ages, frailty as measured using a modification of Fried criteria for frailty was associated with higher risk of death within 1 year in a fully adjusted model (adjusted HR, 2.24; 95% CI, 1.60 to 3.15) (45).…”
Section: Association Of Functional or Cognitive Impairment And Frailtmentioning
confidence: 96%
See 1 more Smart Citation
“…All four studies found a positive association of the presence of frailty with adverse health outcomes. Frailty at dialysis initiation was associated with a higher risk of mortality (45)(46)(47)(48) and hospitalization (45,46,48), independent of age and other possible risk factors for poor outcome. In the largest study in 2275 patients on incident dialysis of all ages, frailty as measured using a modification of Fried criteria for frailty was associated with higher risk of death within 1 year in a fully adjusted model (adjusted HR, 2.24; 95% CI, 1.60 to 3.15) (45).…”
Section: Association Of Functional or Cognitive Impairment And Frailtmentioning
confidence: 96%
“…Four studies assessed frailty and reported a high prevalence of frailty among patients on incident dialysis ranging from 32% to 79% (45)(46)(47)(48). Frailty was measured using different instruments, including two studies using (modified) Fried criteria for frailty (45,46), one using the Clinical Frailty Scale (47), and one using the Groningen Frailty Indicator (48).…”
Section: Association Of Functional or Cognitive Impairment And Frailtmentioning
confidence: 99%
“…Other risk factors for morality in this population were age and being on dialysis. This is consistent with previous literature, which finds frailty is associated with mortality in both pre-dialysis and dialysis patients with CKD (17,28,29,40,44,46,52). The association between FI and mortality was also comparable to previous literature in study populations other than CKD.…”
Section: Discussionsupporting
confidence: 92%
“…However, once this analysis was adjusted for frailty, the relationship between the early dialysis initiation and mortality became non-significant (17). A study by Alfaadel et al further highlighted that frailty at dialysis initiation was independently associated with an increased risk of mortality (52). This indicates that the patient's frailty is the more important predicator of poor outcome from dialysis rather than the time when dialysis is initiated.…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…The agreement between the two reviewers in this paper was .95% for all aspects. The quality of three of 27 studies was good according to all of the established quality criteria (17,22); the remainder of studies was (somewhat) compromised. In 15 studies (56%), the representativeness of the exposed cohort was (somewhat) compromised, because the population proved to be either selected (not black or white race [41] or not $2 years Medicare follow-up before entering the study) or highly selected (exclusion of elderly patients [30], early deaths [43], and one study included 17% prevalent patients who were on chronic hemodialysis before peritoneal dialysis was initiated [24]).…”
Section: Quality Assessmentmentioning
confidence: 99%